2009
DOI: 10.1016/j.aim.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Toric complexes and Artin kernels

Abstract: A simplicial complex L on n vertices determines a subcomplex T_L of the n-torus, with fundamental group the right-angled Artin group G_L. Given an epimorphism \chi\colon G_L\to \Z, let T_L^\chi be the corresponding cover, with fundamental group the Artin kernel N_\chi. We compute the cohomology jumping loci of the toric complex T_L, as well as the homology groups of T_L^\chi with coefficients in a field \k, viewed as modules over the group algebra \k\Z. We give combinatorial conditions for H_{\le r}(T_L^\chi;\… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…Jumping loci of toric complexes. The resonance and characteristic varieties of toric complexes were computed in [46], extending previous results from [44] and [22]. The cohomology group H 1 (T L , k) = k L 1 may be identified with the k-vector space with basis V, denoted k V .…”
Section: Toric Complexes and Right-angled Artin Groupsmentioning
confidence: 76%
See 3 more Smart Citations
“…Jumping loci of toric complexes. The resonance and characteristic varieties of toric complexes were computed in [46], extending previous results from [44] and [22]. The cohomology group H 1 (T L , k) = k L 1 may be identified with the k-vector space with basis V, denoted k V .…”
Section: Toric Complexes and Right-angled Artin Groupsmentioning
confidence: 76%
“…In previous work [46], we showed that the triviality of the monodromy action of Z on i≤k H i (N χ , Q) can be tested in a purely combinatorial way. Moreover, if H 1 (N χ , Q) is a trivial QZ-module, then N χ is finitely generated.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…In [24], we analyze the monodromy action on the homology of Galois Z-covers, for toric complexes associated to finite simplicial complexes. Using Part (2) of the Theorem, we obtain a combinatorial criterion for the full triviality of this action, up to a given degree.…”
Section: 2mentioning
confidence: 99%